GREEN HOTEL : TINJAUAN KONSEP DAN PRAKTEKNYA DI INDONESIA - Yuniati, Nining (Kepariwisataan: Jurnal Ilmiah, 2017)
Green hotel is so far still less popular and more commonly known as a mere of concept. This paper attempts to express what is meant by green hotel and how itspracticed in the hospitality industry, in Indonesia. Currently, Indonesia has had annual agenda i.e National Green Hotel Award, which was initiated by the government to support the campaign of practice of green hotel. Its also respond to the market trend which increasingly concerned about the environment. Keyword: green hotel, implementation, new tourism